Pengaruh Pengetahuan Perpajakan Dan Religiusitas Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Pelaku Ekonomi Kreatif Sub Sektor Blended Fashion Dan Kuliner Di Kota Malang - Rifqina Qanita; Jeni Susyanti; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of the research was to find out the influence of taxation knowledge and religiosity on the compliance of individual taxpayers on creative economy actors of the blended fashion and culinary sub-sector in Malang City. The determination of samples in the study is using purposive sampling techniques, so that it can be determined the number of samples as many as 50 respondents who meet the criteria. The analytical tool used in this study is multiple linear regression analysis. The results showed that knowledge of taxation and religiosity simultaneously have a significant effect on the compliance of private taxpayers on creative economy actors blended fashion and culinary sub-sector in malang city. The variables of tax knowledge have a significant and positive effect on the compliance of individual taxpayers in the creative economy actors of the blended fashion and culinary sub-sector in Malang City. The variable religiosity has no effect on the compliance of private taxpayers in the creative economy actors of the blended fashion and culinary sub-sectors in Malang. Keywords: Creative Economy Actors Blended Fashion and Culinary Sub Sector in Malang City, Knowledge taxation, Religiosity, Taxpayer Compliance.